PERKAWINAN ANTAR PEMELUK AGAMA DI INDONESIA - AFRIAN RAUS (Institut Agama Islam Negeri Batusangkar, 2016)
The Acts Number 1 Year 1974 does not directly discuss about the marriage of future couple coming from different religious beliefs. Consequently, such marriage cannot be done in Indonesia following Chapter 2 verse 1 and Chapter 8 part f and supported by the opinions of other relegions (i.e Catholic, Protestant, Buddha and Hindu). However, such marriage can be accommodated as long as it is done in other country where it is allowed by its rules and officially registered to Civil Registration office in Indonesia.Kata kunci: perkawinan, beda, agama